On the Bright Path: Female Labor in the Food Industry in 1954-1964 (based on Materials from the Krasnoyarsk Territory) - N. V. Gonina; R. V. Pavlyukevich; A. Yu. Vavilenko (Научный диалог)
The relevance of the work is due to the preservation of the problems of the Soviet period in a number of modern industries. The issue of female labor conditions is considered on the example of the food industry of the Krasnoyarsk Territory in the Khrushchev decade. The novelty of the study is seen in the fact that the problem of female labor in industry was considered only from the point of view of the Soviet concept; little attention is paid to it in modern literature. The authors dwell on the characteristics of the difficult conditions of female labor in enterprises of local importance. The author’s inference of the reasons why women not only agreed to work in uncomfortable conditions but also considered their situation to be beneficial is presented. It is shown that work in the food industry, which gives the opportunity of free access to food in the conditions of a shortage of goods was desirable. It is also noted that in this industry high requirements were not demanded on the qualifications of women workers, which suited women who were not educated and burdened by their families. It is emphasized that the “sphere of female labor” is a concept created in the Soviet economy with the aim of involving women in production and symbolizing the state’s concern for the health and well-being of women. It is proved that in reality the sphere of female labor has become a place of segregation and a zone of preservation of primitive forms of management.